A single-round selection of selective DNA aptamers for mammalian cells by polymer-enhanced capillary transient isotachophoresis. Issue 21 (6th September 2017) - Hirose, Kazuki; Tsuchida, Maho; Asakura, Hinako; Wakui, Koji; Yoshimoto, Keitaro; Iida, Keisuke; Sato, Makoto; Shibukawa, Masami; Suganuma, Masami; Saito, Shingo
Abstract : A single-round DNA aptamer selection for mammalian cells was successfully achieved for the first time using a capillary electrophoresis (CE)-based methodology. Abstract : A single-round DNA aptamer selection for mammalian cells was successfully achieved for the first time using a capillary electrophoresis (CE)-based methodology called polymer-enhanced capillary transient isotachophoresis (PectI). The PectI separation yielded a single peak for the human lung cancer cell line (PC-9) complexed with DNA aptamer candidates, which was effectively separated from a free randomized DNA library peak, ensuring no contamination from free DNA in the PC-9–DNA aptamer complex fraction. The DNA aptamer candidates obtained after a single-round selection employing counter selection with HL-60 were proven to bind selectively and form kinetically stable complexes with PC-9 cells. Interestingly, most aptamer candidates showed high binding ability ( K d = 70–350 nM) with different extents of binding on the cell surface. These facts proved that a single-round selection for mammalian cells by PectI is feasible to obtain various types of aptamer candidates, which have high-affinity even for non-overexpressed but unique targets on the cell surface in addition to overexpressed targets.